Effect of Government Spending, GRDP and Investment on Income Inequality in Islamic Economics - Selvyta Ramadhini; Muhammad Yusuf Bahtiar; Adib Fachri (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the effect of government spending, GRDP and investment on income inequality in Indonesia: The Islamic Economic Perspective Study on the area of Sumatra island in 2014-2023. Methodology/approach: The objective of this descriptive-verification quantitative study is to analyze cause-and-effect relationships and test the hypothesis of the effect of government spending, GRDP, and investment on income inequality (Gini ratio) in all provinces of Sumatra Island from 2014 to 2023. Result: That government spending and GRDP partially negatively influence income inequality in Indonesia, but investment does not affect income inequality in Indonesia. Conclusion: From an Islamic economic perspective, this inequality can be analyzed through the principles of distributive justice, social welfare, and Islamic economic instruments such as zakat, infaq, sadaqah, and waqf. Islamic economics emphasizes the principle of justice in income distribution and social welfare. Islam prohibits inequality and consistently emphasizes justice, as stated in the word of Allah in Surah Al-Hasyr verse 7, which states that Islam strictly forbids the concentration of wealth in the hands of only a few. Limitation: This research is only focused on the Sumatra Island region, which includes provinces such as Aceh, North Sumatra, West Sumatra, Riau, Riau Islands, Jambi, Bengkulu, South Sumatra, Bangka Belitung, and Lampung. Contribution: This research enriches the scientific literature in the field of development economics and Islamic economics by examining the relationship between government expenditure, Gross Regional Domestic Product (GRDP), and investment on income inequality, particularly in the Sumatra Island region during the period 2014–2023.